Effect of massage on the success of anesthesia and infiltration injection pain in maxillary central incisors: Double-blind, crossover trial - Roohollah Sharifi; Saber Khazaei; Hamid R Mozaffari; Seyed M Amiri; Pedram Iranmanesh; Seyed A Mousavi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Pain control is important during dental treatments since the lack of sense of pain causes less emergency events, less extra injections, and increased patient's trust. Infiltration injection in the anterior maxilla was considering one of the most painful injections. The aim of this study was to investigate the effect of local massage on the success of anesthesia and infiltration injection pain in maxillary central incisors. Materials and Methods: This double-blind, crossover trial was conducted among 30 participants by injection with and without "massage before the injection" over two sessions with an interval of 2 weeks. The injection pain in both methods was measured immediately after injection by Visual Analogue Scale (VAS) at three times of needle insertion, 5 seconds after injection, and needle withdrawal. The success rate of anesthesia was determined 5, 15, and 30 minutes after injection by electrical pulp tester. Results: The mean scores of VAS at three times with and without the massage at three times were not statistically significant (Wilcoxon, P > 0.05). However, the mean score of VAS in injection with the massage were lower. The success of anesthesia in injection with and without the massage at intervals 5, 15, and 30 minutes after injection was not found to be significant (McNamara, P > 0.05). Conclusion: Massage before injection had no effect on the success of anesthesia and injection pain.